INFLUENCE OF THE COMPONENTS OF THE WINDOW ON THERMAL CONDUCTIVITY - Jevtoska, Elena; Gruevski, Gjorgi (Innovation in Woodworking Industry and Engineering design, 2024)
The purpose of the windows as a construction product is to provide the building with natural light and the opportunity to ventilate the interior and at the same time providing protection to the room against external influences such as wind and rain, as well as to prevent uncontrolled cooling or heating of the room or the whole building in which they are built in. A window is a complex product which is constructed of different parts that could be made of different materials. In addition to providing light and protection from external influences such as rain and wind, the window has a key part in the energy efficiency of buildings. Energy efficiency as a term is usually associated in with two separate approaches, energy effects of devices and energy efficiency measures. When it comes to an energy-efficient device, then it is the device that has a high degree of energy utilization, while measures related to energy efficiency are all that we can do to reduce energy consumption. In order to protect the energy of the buildings, among other things, well-chosen windows of good quality and their proper installation play a key role in it. This research is focused on how much the component parts of the window have an influence on the thermal conductivity of the entire window, in fact, how different combinations of profiles that are used and glass packages affect the coefficient of thermal conductivity of the windows.